Longitudinal phenotypic analysis of human immunodeficiency virus type 1-specific cytotoxic T lymphocytes: correlation with disease progression. - Ogg, G; Kostense, S; Klein, MR; Jurriaans, S; Hamann, D; Mcmichael, A; Miedema, F (1999)
Few studies have examined longitudinal changes in human immunodeficiency virus type 1 (HIV)-specific cytotoxic T lymphocytes (CTL). To more closely define the natural history of HIV-specific CTL, we used HLA-peptide tetrameric complexes to study the longitudinal CD8(+) T-cell response evolution in 16 A*0201-positive untreated individuals followed clinically for up to 14 years. As early as 1 to 2 years after seroconversion, we found a significant association between high frequencies of A*0201-restricted p17(Gag/Pol) tetramer-binding cells and slower disease progression (P < 0.01). We observed that responses could remain stable over many months, but any longitudinal changes that occurred were typically accompanied by reciprocal changes in RNA viral load. Phenotypic analysis with markers CD45RO, CD45RA, and CD27 identified distinct subsets of antigen-specific cells and the preferential loss of CD27(+) CD45RO(+) cells during periods of rapid decline in the frequency of tetramer-binding cells. In addition we were unable to confirm previous studies showing a consistent selective loss of HIV-specific cells in the context of sustained Epstein-Barr virus-specific cell frequencies. Overall, these data support a role of HIV-specific CTL in the control of disease progression and suggest that the ultimate loss of such CTL may be preferentially from the CD27(+) CD45RO(+) subset.